Evaluation of Welding Current Impact on Residual Stresses Status in Ship-Building Steel Weldments Using Barkhausen Noise (The International Journal of Engineering & Information Technology (IJEIT), 2024)
The paper intends to determine the relationship between heat input and the residual stresses distribution in shipbuilding steel weldments using the Magnetic Barkhausen Noise (MBN) technique. The rate of fusion during welding was controlled by amount and time of fusion for a given weld bead width. Barkhausen noise measurements were performed parallel to the weld bead at the back of the plates welded using variable welding currents along the line that crosses the weld bead. The heat affected zones were differentiated by a variation in MBN peak height. The high welding current was characterized by high MBN amplitude compared with the medium and the low currents. The results showed that the heat affected zone was narrower with high welding current and increases with decreasing current. The results indicate that residual stresses introduced in steel by welding could be mapped nondestructively by magnetic Barkhausen noise.